IDENTIFIKASI KERAGAMAN MOLEKULER MATERIALGENETIK KELAPA SAWIT (Elaeis guineensis Jacq.) BERDASARKAN MARKA SSR (Simple Sequence Repeats) - Indra Syahputra (Jurnal Pertanian Tropik, 2017)
Oil Palm very important for Indonesia. The plant breeding programs were done to found thebest varieties. The identification of molecular variants is the one step of plant breeding programs.The purpose of this research was to analysis molecular variants of the genetic material of oil palm-based on 4 SSR markers, there were mCnCIR0038, mEgCIR0894, mEgCIR3292 and mEgCIR3663. DARwin 6.0 was used to analysis of the data. The results of this research showedthat genetic molecular variants based on SSR markers were 41.68%.